A contribution to the study of the genus Cadomella OEhlert and OEhlert, 1887 (Brachiopoda, Jurassic) - Halamski , Adam T.; Baliński, Andrzej (Acta Geologica Polonica, 2026)
On the basis of a biometric analysis of German and English representatives of the peculiar Early Jurassic rhynchonellate brachiopod Cadomella, two species, the early Toarcian C. moorei (Davidson in Davidson and Morris, 1847) and the late Pliensbachian C. quenstedti Rau, 1905, are considered as synonyms. Moreover, a certain number of misinterpretations concerning the genus is corrected. Its authorship belongs to Daniel and Pauline Oehlert (15 June 1887) and not to Ernest Munier-Chalmas (not earlier than 30 June 1887), even if the latter orally presented the new genus along with its name at the meeting on 23 February 1887. The distribution of the monotypic genus Cadomella includes the upper Pliensbachian of Germany and the lower Toarcian of England, France, and North Africa. The Cadomellidae are undoubted rhynchonellates, but their further affinities are still enigmatic: there exist several similarities with some thecideides (concavo-convex shell, dorsal valve features), but important differences (impunctate vs. endopunctate microstructure) occur as well.